2021
DOI: 10.1002/ptr.7034
|View full text |Cite
|
Sign up to set email alerts
|

Piper nigrum extract attenuates food allergy by decreasing Th2 cell response and regulating the Th17/Treg balance

Abstract: Piper nigrum is extensively utilized because of its antioxidation, antiallergic, antitumor, antiinflammatory, antidiarrhea, and gastrointestinal protection. We attempted to indicate whether the Piper nigrum extract (PNE) could alleviate ovalbumin (OVA)-induced food allergy, and to explore its potential mechanism. An OVA-induced food allergy mouse model was established, and different concentrations of PNE were administrated. Symptoms of food allergy, levels of immunoglobulin E (IgE), mucosal mast cell protease-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…4 The increase in sIgE, Th2-type, and Th17-type inflammatory cytokines induces inflammatory infiltration of the intestinal tract and leads to the clinical symptoms of FA. [5][6][7][8][9] Probiotics have been reported to alleviate FA by modulating the immune response of the host body. A probiotic mixture decreased the secretion of IgE and Th2 cytokines (IL-4, IL-5, IL-10, and IL-13) in OVA-induced FA alleviation.…”
Section: Introductionmentioning
confidence: 99%
“…4 The increase in sIgE, Th2-type, and Th17-type inflammatory cytokines induces inflammatory infiltration of the intestinal tract and leads to the clinical symptoms of FA. [5][6][7][8][9] Probiotics have been reported to alleviate FA by modulating the immune response of the host body. A probiotic mixture decreased the secretion of IgE and Th2 cytokines (IL-4, IL-5, IL-10, and IL-13) in OVA-induced FA alleviation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Th2-mediated inflammatory responses were exacerbated in Tregs-deficient mouse models [65]. Furthermore, animals with food allergy model also showed enhanced Th2 cell response, inhibited Treg cell expansion, and significantly increased Th17/Treg ratio [66]. These findings confirm that early gut microbiota changes can affect the proliferation and induction of Treg cells and thus the forming of gut homeostasis.…”
Section: Gut Microbiota Enhances Immune Tolerance Bymentioning
confidence: 55%
“…44 Wang et al revealed that Piper nigrum extract tends to play a protective role in OVA-induced FA by suppressing Th2 cell response and adjusting Th17/Treg balance. 45 Diosgenin was also demonstrated to attenuate allergic reactions in OVA-allergic mice by repression of MC infiltration and degranulation pathways. 46 According to the present results, dramatically promoted the secretion of IL-10 and reduced histamine levels were observed when the sensitized mice were supplied with β-sitosterol.…”
Section: Discussionmentioning
confidence: 99%